Profil Perilaku Altruistik Mahasiswa dan Implikasinya terhadap Program Pelatihan Kompetensi Kepribadian Calon Konselor - Rina Yulitri; Ardimen; Emeliya Hardi; Gustina (Universitas Kanjuruhan Malang, 2020)
The purpose of this study is to describe the altruistic behavior of student guidance and counseling. This type of research is quantitative descriptive. The population of this research is the students majoring in guidance and counseling at IAIN Batusangkar. Sampling with a purposive sampling technique, namely 7 semester 74 students. The results of this study indicate that only a small proportion of students possess altruistic behavior at high and very high classifications. While altruistic behavior in the aspect of wanting to give, empathy, volunteering, helping others, prioritizing others, and feeling the results are good for those who are helped and helped are in the medium classification.